Metody eksterminacji gryzoni w przekazach antycznych agronomów (Rodent Extermination Methods in the Accounts of Ancient Agronomists) - Bartnik, Agnieszka (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2024)
In ancient times, rodents were a major problem causing economic losses and an epidemiological threat due to the bacteria and parasites they carried. Ancient authors primarily mentioned field mice and house mice, which ate the grain, contaminated the land and food intended for humans and animals, and caused damage within the house and farm buildings. Most of the advice preserved from those times was on how to exterminate rodents, with only few texts providing recommendations on how to protect farm buildings and grain from mice. Ancient poison formulas primarily relied on poisonous plants and were usually served in cake form or added to food. There are some differences within the recommended poisons. More toxic substances were used in the farmyard and outbuildings than in the houses, which probably has to do with the risk that these poisons, due to their composition, posed to people and especially children.